«Credo quia absurdum»:Obscurantism and Destructive Religiosity in Modern Culture - Boretsky, O. M.; Kim, L. M. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
The article discuses the phenomenon of false forms of religiosity from a perspective of the destructive influence of faith on an individual in contemporary culture. The object of the analysis is the so-called «religious rebirth». Special attention is given to some aspects of religious proselytism, psychological mechanism of involvement into a totalitarian sect, as well as main needs of an individual satisfaction of which affects the individual’s choice of becoming a member of this or that religious group. The authors attempted to uncover the reasons of existence of modern obscurantism and false forms of religiosity, justify the need for «new century Education» and relevance of secular ethics.